Atrial function is altered in lone paroxysmal atrial fibrillation in male endurance veteran athletes. (23rd October 2017) - Hubert, Arnaud; Galand, Vincent; Donal, Erwan; Pavin, Dominique; Galli, Elena; Martins, Raphaël P; Leclercq, Christophe; Carré, François; Schnell, Frédéric
Abstract: Aims: Intensive endurance sport practice is associated with an increased risk of atrial fibrillation (AF) in male veteran athletes. Paroxysmal AF (PAF) is the very beginning step of this disease. The description of atrial remodelling occurring at this early stage might enable to depict predictive factors of AF in veteran athletes in order to give them personalized recommendation according to their sport practice. Methods and results: Twenty-seven male endurance veteran athletes with documented PAF were retrospectively enrolled and compared with 30 control endurance athletes without documented AF, with similar training level, age, and cardiovascular risk factors. All subjects underwent a resting-electrocardiogram (ECG) to assess the electric remodelling of P-waves as well as an echocardiography, to evaluate the left and right atrial (LA, RA) anatomical and functional (assessed by 2D strain) remodelling. No difference was noted between groups for the ECG P-wave parameters. Atrial function was decreased in the PAF group, particularly the peak atrial longitudinal strain (L-ɛ-Max) of LA (29.3 ± 7.9% vs. 49.1 ± 7.8% respectively in the PAF group and in controls, P < 0.0001) and RA (36.5 ± 7.0% vs. 50.6 ± 10.2%, P < 0.0001). LA and RA volumes were also larger in the PAF group. Receiver operating characteristic analysis demonstrated that L-ɛ-Max of LA [area under curve (AUC): 0.957 ± 0.023] and RA (AUC: 0.901 ± 0.042) had the best ability to identify the athletes with PAF, far better than the anatomical parameters (AUC < 0.75 in all). Conclusion: Atrial function analysed by strain in echocardiography is strongly associated with PAF and might enable to identify male endurance veteran athletes at risk to develop AF.